IDENTIFICATION AND QUANTIFICATION OF CRITICAL FACTORS SHAPING THE LEARNING EXPERIENCE OF STUDENTS IN A HIGHER EDUCATION INSTITUTION IN OMAN - Dr. Priy Brat Dwivedi (PUPIL: International Journal of Teaching, Education and Learning, 2025)
Aim: This research aims to identify and quantify the factors shaping the learning experiences of students at the College of Engineering, National University of Science and Technology, Oman, particularly in the context of the rise of AI chatbots. Method: A total of 22 students from levels 3 and 4 were selected for focus group interviews conducted in a regular classroom setting. A set of 34 questions was designed based on Urie Bronfenbrenner’s updated ecological systems theory. The responses were digitized for both quantitative and qualitative analysis. Main Findings: The results indicate a high awareness among students regarding the importance of achieving a place on the dean’s list and the role of AI and machine learning in future education. However, there was low awareness of online library services, MOOCs, and job prospects. Mixed responses were recorded concerning peer tutoring, group assignments, and participation in student clubs. Notably, students expressed a positive attitude toward using social media for study purposes. Implications: These findings are crucial for understanding the pain points and challenges contributing to poor learning experiences and low awareness among students. The insights gained can assist college management in addressing these issues and enhancing the overall learning experience. Novelty: This study offers a novel exploration of the factors affecting students’ learning experiences in a post-COVID-19 context, providing valuable information that can lead to improved educational strategies at the college level.